Methods for Assessing the Effectiveness of Russian Regional Transport and Logistic Systems of Road Freight - Georgiy Greyz; Julia Kuzmenko; Tatyana Konovalova; Irina Smirnova; Ruslan Turlayev (Communications of International Proceedings, 2020)
The article deals with the analytical methods for performance evaluation of regional transport and logistics systems of trucking. To evaluate the functioning of regional transport and logistics systems, 4 groups of key indicators are applied: 1. Geopolitical indicators 2. Economic indicators 3. Infrastructure indicators 4. Logistic indicators. These methods provide an integral evaluation (rating) for each group of indicators on the basis of individual indicators. The mathematical methods of the fuzzy set theory are proposed for the integral evaluation of the transport and logistics systems performance. These methods provide adequate evaluation of heterogeneous information about the condition of transport and logistics systems. The analytical methods make it possible to obtain a comparative performance evaluation of various transport and logistics systems.
Keywords: Logistics; Regional Transport and Logistics Systems; Trucking; Key Performance Indicators Groups; Performance Evaluation Methods; Fuzzy Sets Theory.